The Bacterial and pathogenic landscape of African buffalo (Syncerus caffer) whole blood and serum from Kenya - Richard Nyamota; Earl A. Middlebrook; Hussein M. Abkallo; James Akoko; Francis Gakuya; Lillian Wambua; Bernard Ronoh; Isaac Lekolool; Athman Mwatondo; Mathew Muturi; Bernard Bett; Jeanne M. Fair; et al. (Animal Microbiome)
Abstract Background African buffalo (Syncerus caffer) is a significant reservoir host for many zoonotic and parasitic infections in Africa. These include a range of viruses and pathogenic bacteria, such as tick-borne rickettsial organisms. Despite the considerations of mammalian blood as a sterile environment, blood microbiome sequencing could become crucial for agnostic biosurveillance. This study investigated the blood microbiome of clinically healthy wild buffaloes in Kenya to determine its applicability in agnostic testing for bacteria in apparently healthy wild animals. Methods Whole blood and serum samples were collected from 46 wild African buffalos from Meru National Park (30), Buffalo Springs (6) and Shaba (10) National Reserves in upper eastern Kenya. Total deoxyribonucleic acid (DNA) was extracted from these samples and subjected to amplicon-based sequencing targeting the 16 S rRNA gene. The bacteria operational taxonomic units (OTU) were identified to species levels by mapping the generated V12 and V45 regions of 16 S rRNA gene to the SILVA database. These OTU tables were used to infer the microbial abundance in each sample type and at the individual animal level. The sequences for the corresponding OTUs were also used to generate phylogenetic trees and thus infer evolution for the OTUs of interest. Results Here, we demonstrate that buffaloes harbor many bacteria in their blood. We also report a diversity of 16 S rRNA gene sequences for Anaplasma and Mycoplasma from individual animals. By sequencing both whole blood and serum in triplicate for each animal, we provide evidence of the differences in detecting bacteria in both sample types. Conclusions Diverse bacteria, including some potential pathogens, can be found in the blood of clinically healthy wild African buffalo. Agnostic surveillance for such pathogens can be achieved through blood microbiome sequencing. However, considerations for the question being asked for the blood microbiome in wildlife will impact the choice for using whole blood or serum for sequencing.